New species of Glenophisis (Orthoptera: Tettigoniidae: Hexacentrinae) from Singapore, with key to species - Tan, Ming Kai (Zootaxa, 2012)
One new species of Glenophisis from Singapore is described: Glenophisis singapura sp. n. Key to the species of Glenophisis is also provided.